A composite carbon source and its preparation method and application

By combining artificial polymer PHA with agricultural waste, a composite sustained-release carbon source is prepared, which solves the problem of insufficient optimization of mixed carbon source preparation conditions and material ratio in the prior art, and achieves efficient wastewater treatment and cost reduction.

CN119161016BActive Publication Date: 2025-04-25PEARL RIVER FISHERY RES INST CHINESE ACAD OF FISHERY SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411285684.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-04-25
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

When using mixed carbon sources to treat wastewater, there are few researches on preparation conditions and material ratio optimization, resulting in poor performance and high cost of solid carbon sources.

Method used

Using artificial polymer PHA and agricultural waste (such as corn crust and rice poles), a composite sustained-release carbon source is prepared through the use of hydrogel skeletons and crosslinking agents, and its performance and economy are improved by optimizing proportion and process conditions.

Benefits of technology

The efficient denitrification and denitrification performance of composite carbon sources in aquaculture tail water treatment is achieved, which reduces material costs and improves the microbial diversity of sludge through the optimization of microbial community structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161016B_ABST
    Figure CN119161016B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite carbon source and a preparation method and application thereof, which belongs to the field of material technology, and comprises the following steps: adding an artificial polymer PHA and agricultural waste to a hydrogel skeleton, adding the resultant to a cross-linking agent for cross-linking after freeze-forming, and then drying after washing to obtain the composite slow-release carbon source. The present invention also discloses a composite carbon source prepared by the above-mentioned preparation method and its application in denitrification. The present invention combines the performance complementary materials (corn husk, rice stalk, PHA) screened in the previous study to prepare a mixed carbon source, optimize the current preparation conditions, and use 3D-EEM, SEM, FTIR and other means to analyze the characteristics of the leaching solution and the material itself, and subsequently explore the optimized ratio of the mixed solid carbon source complementary materials, improve the performance of the solid carbon source and reduce its cost, and provide suitable materials for aquaculture tail water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology, and in particular relates to a composite carbon source and a preparation method and application thereof. Background Art

[0002] At present, most domestic and foreign scholars use natural carbon-containing materials or artificially synthesized biodegradable polymers as a single solid carbon source to treat sewage. At present, some scholars have tried to combine the two types of materials to prepare mixed carbon sources. For example, Li et al. mixed starch with PVA to prepare a solid carbon source with a denitrification efficiency of up to 94.6%; Zou et al. used corn cobs and PHB as carbon sources to prepare composite materials, and found that they have high stability and absorbency. By releasing carbon and absorbing attached denitrifying bacteria, the total nitrogen removal rate increased by more than 48.56%; Xiong et al. used peanut shells and PCL as the main materials and polyvinyl alcohol-sodium alginate (PVA-SA) as a hybrid scaffold to synthesize a slow-release carbon source with good carbon release and denitrification performance. At the same time, it was found that after adding a mixed carbon source, the diversity of microorganisms in the sludge was reduced, and the dominant denitrifying strains such as Proteus (Gammaprotobacteria) were enriched (relative abundance increased from 39.32% to 46.66%). However, there is little research on the preparation conditions and material ratio optimization of mixed carbon sources. Summary of the invention

[0003] In order to solve the above technical problems, the present invention proposes a composite carbon source and a preparation method and application thereof.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing a composite carbon source comprises the following steps:

[0006] The artificial polymer PHA and agricultural waste are added to the hydrogel skeleton, and after freeze-forming, they are added to the cross-linking agent for cross-linking, and then washed and dried to obtain the composite slow-release carbon source.

[0007] Preferably, the agricultural waste includes corn husk carbon source and / or rice straw carbon source.

[0008] Preferably, the mass ratio of the artificial polymer PHA to the agricultural waste is (1-3): (3-1).

[0009] Preferably, the hydrogel skeleton is a polyvinyl alcohol-sodium alginate hydrogel skeleton, and the specific preparation method comprises the following steps:

[0010] The polyvinyl alcohol and sodium alginate are mixed, water is added and stirred evenly, the mixture is heated in a water bath once, then allowed to stand, and then heated in a water bath twice to obtain the polyvinyl alcohol-sodium alginate hydrogel skeleton.

[0011] Preferably, the mass ratio of polyvinyl alcohol, sodium alginate and water is 32:3:400.

[0012] Preferably, the temperature of the water bath heating is 95°C and the time is 10 minutes;

[0013] The temperature of the secondary water bath heating is 95°C and the time is 15 to 20 minutes;

[0014] The standing time is 12 hours.

[0015] Preferably, the cross-linking agent is a saturated H3BO4 solution containing 5% CaCl2.

[0016] Preferably, the cross-linking temperature is 4° C. and the time is 24 h.

[0017] A composite carbon source prepared by a method for preparing a composite carbon source.

[0018] The invention discloses an application of a composite carbon source in aquaculture tail water treatment.

[0019] Compared with the prior art, the present invention has the following advantages and technical effects:

[0020] The present invention combines complementary materials (corn husk, rice stalk, PHA) screened in previous studies to prepare a mixed carbon source, optimizes the current preparation conditions, and uses 3D-EEM, SEM, FTIR and other methods to analyze the properties of the leachate and the material itself. Subsequently, the optimal ratio of the complementary materials of the mixed solid carbon source is explored to improve the performance of the solid carbon source and reduce its cost, thereby providing suitable materials for aquaculture tail water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0022] Figure 1 Composite carbon source preparation process flow chart;

[0023] Figure 2 This is the COD release and TN pollution release diagram of the composite carbon source;

[0024] Figure 3 The composite carbon source promotes the denitrification effect of SAT; Figure (a) and (b) are the NO3 in SAT after adding composite carbon sources containing CH and RS respectively. - -N removal rate; Figures (c) and (d) are respectively the NH4 in SAT after adding composite carbon sources containing CH and RS + -N removal rate; Figures (e) and (f) are the TN removal rates in SAT after adding composite carbon sources containing CH and RS, respectively;

[0025] Figure 4 The distribution of OTU number of sludge microorganisms after denitrification experiment with CH and RS composite carbon sources;

[0026] Figure 5 Relative abundance of bacteria at the phylum (a) and genus (b) levels in sludge after denitrification experiment with combined carbon sources containing CH;

[0027] Figure 6 Relative abundance of bacteria at the phylum (a) and genus (b) levels in sludge after denitrification experiment with composite carbon source containing RS;

[0028] Figure 7 Scanning electron micrographs of CH2 and RS3 before and after carbon release and denitrification. Figures (a) and (b) are the initial surface structures of CH2 and RS3 composite carbon source materials, respectively; Figures (c) and (d) are the surface structures of CH2 and RS3 composite carbon source materials after carbon release, respectively; Figures (e) and (f) are the surface structures of CH2 and RS3 composite carbon source materials after denitrification, respectively;

[0029] Figure 8 The three-dimensional fluorescence spectrum (3D-EEM) of the leachate before and after denitrification of composite carbon sources CH2 and RS3;

[0030] Fig. 9 FTIR spectra of composite carbon sources CH2 and RS3 at different stages. (a) C1 is the initial state, C2 and C3 are the carbon source materials after carbon release and denitrification, respectively; (b) R1 is the initial state, R2 and R3 are the carbon source materials after carbon release and denitrification, respectively;

[0031] Fig.10 The results of the reactor with CH2 as filler at different HRTs are shown in Figure 2. - -N, TN removal rate;

[0032] Fig.11 NO2 after denitrification in reactors with CH2 as filler at different HRTs - -N accumulation;

[0033] Fig.12 The results of the reactor with RS3 as filler at different HRTs were shown in Figure 2. - -N, TN removal rate;

[0034] Fig.13 NO2 after denitrification in reactors with CH2 as filler at different HRTs - -N accumulation;

[0035] Fig.14 The distribution of microbial OTU numbers after denitrification experiments in reactors with CH2 and RS3 as fillers;

[0036] Fig.15 is the relative abundance of bacteria at the phylum level in the sludge after the denitrification experiment in the reactor with CH2 and RS3 as fillers;

[0037] Fig.16 Relative abundance of bacteria at the genus level in sludge after denitrification experiment in reactors with CH2 and RS3 as fillers. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0040] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;

[0041] Wherein, polyvinyl alcohol (PVA) was analytically pure, with a degree of alcoholysis of 98-99 mol%, and a viscosity of 3.2-3.8 mPa.s, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0042] Sodium alginate (SA) of high purity was purchased from Sangon Biotech (Shanghai) Co., Ltd.;

[0043] Rice stalks were collected from farms in Qingyuan City, Guangdong Province; corn husks were collected from Lilang Agricultural and Sideline Products Wholesale Market in Guangzhou City, Guangdong Province. After the agricultural waste was collected, it was cut into small segments of 3 to 4 cm, and then repeatedly rinsed with ultrapure water to remove surface impurities, and placed in an oven for constant temperature drying for 24 hours, the temperature was set to 60°C, and then ground with a pulverizer, and crushed through an 18-mesh sieve to obtain the desired powder, with a particle size of less than 1 mm. The sieved material was dried in an oven at 60°C until the weight was constant, and then stored in a sealed bag at 4°C to obtain the corn husks and rice stalks used in Examples 1 and 2 of the present invention.

[0044] The room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.

[0045] Example 1

[0046] A method for preparing a composite carbon source, such as Figure 1 As shown, the following steps are included:

[0047] (1) Preparation of cross-linking agent: The cross-linking agent is a saturated H3BO4 solution containing 5% CaCl2. 150 g H3BO4 is weighed and placed in a 2 L beaker. 2 L ultrapure water is added and heated and stirred until completely dissolved to obtain a saturated boric acid solution. 100 g CaCl2 is then added and stirred until completely dissolved to complete the preparation of the cross-linking agent. The cross-linking agent is stored in a 4°C refrigerator and used after the temperature drops to 4°C.

[0048] (2) Polyvinyl alcohol-sodium alginate (PVA-SA) hydrogel skeleton: Select a 500 ml beaker, weigh 32 g PVA and 3 g SA, mix them, add 400 ml ultrapure water, and stir evenly with a glass rod. Seal the beaker with tin foil to reduce water evaporation. Heat in a 95 °C water bath for 10 min. After standing for 12 h, heat in a water bath to 95 °C again to help quickly and completely dissolve and reduce water loss to obtain a hydrogel skeleton (PVA-SA skeleton).

[0049] (3) Preparation of carbon source mixture: corn husk and artificial polymer PHA in different mass ratios were added to the PVA-SA skeleton obtained in step (2), and stirred evenly in a water bath at 95° C. The amounts of PHA and corn husk were grouped as shown in Table 1:

[0050] serial number CH1 CH2 CH3 CH4 CH5 Quality Ratio 1:3 1:2 1:1 2:1 3:1 PHA 16g 21.3g 32g 42.7g 48g Corn Husk 48g 42.7g 32g 21.3g 16g

[0051] (4) Freeze molding: Pour the evenly stirred PVA-SA skeleton and the mixture into a 1 cm*1 cm*1 cm square mold and freeze it in a -20 °C refrigerator for 24 h to fix the shape;

[0052] (5) Low-temperature cross-linking: The frozen molded material was demolded and immediately placed in a cross-linking agent containing 5% CaCl2 saturated H3BO4 solution cooled to 4°C in advance, and cross-linked at 4°C for 24 hours;

[0053] (6) Washing and drying: The cross-linked carbon source is soaked and washed three times with ultrapure water to remove surface impurities and residual H3BO4. The washed carbon source is dried at 60°C and stored in a sealed bag at 4°C for later use, thereby obtaining a composite carbon source CH group (CH1, CH2, CH3, CH4, CH5).

[0054] Example 2

[0055] The difference from Example 1 is that an equal amount of corn husks was replaced with rice straws, and the resulting composite carbon sources (RS group) were recorded as RS1, RS2, RS3, RS4 and RS5 according to the mass ratios of PHA to rice straw of 1:3, 1:2, 1:1, 2:1 and 3:1, respectively.

[0056] Technical effects:

[0057] 1. Test methods

[0058] (1) Static release test:

[0059] Both the static release experiment and the static denitrification experiment were carried out in a 250 ml conical flask.

[0060] Static release experiment: Weigh 1g of each of the 10 composite carbon sources obtained in Examples 1 and 2 and put them into 250ml conical flasks, then add 250ml of ultrapure water to the conical flasks, and seal each conical flask with a rubber stopper. The experiment was carried out at room temperature (22±2°C) under light shielding. Three replicates were set for each carbon source, and water samples were collected at 4, 8, 12, 24, 48, 72, 96, 120, 144, and 168 hours. Each time, 5ml of water sample was aspirated from each conical flask with a pipette and the hydration index was measured. After each sampling, the same volume of ultrapure water was added and shaken well.

[0061] Static denitrification experiment: The denitrification experiment steps are the same as the static release, 250 ml of ultrapure water is replaced with synthetic aquaculture tail water, and 2 ml of denitrification sludge is added to the conical flask. A no-carbon source control group is added, and the rest of the operations are the same as the experimental group except that no carbon source is added.

[0062] (2) Weigh 1g of each of the 10 composite carbon sources obtained in Examples 1 and 2 and put them into a 1000ml conical flask, then add 1000ml of synthetic aquaculture tail water SAT to the conical flask, and then add 2ml of denitrification sludge. Each conical flask is sealed with a rubber stopper. Two control groups were set up, one group was a blank group, recorded as the sludge control group, and the other group was a group that only added PVA-SA skeleton as a carbon source without adding agricultural waste and polymer, recorded as the PVA-SA control group. The experiment was carried out at room temperature (22±2°C) under light shielding. Three replicates were set for each group, and water samples were collected at 4, 8, 12, 24, 48, 72, 96, 120, 144, and 168 hours. Each time, 5ml of water sample was aspirated from each conical flask with a pipette and the hydration index was measured. After each sampling, the same volume of ultrapure water was added and shaken well.

[0063] (3) The samples in the initial state of the optimal carbon source ratio, after the 7-day static release experiment, and after the 7-day denitrification test were dried and sputtered with gold, and the surface structure was observed using a field emission scanning electron microscope (SEM).

[0064] (4) Fourier transform infrared spectroscopy (FTIR) was used to observe and analyze the status and changes of functional groups, chemical bonds and molecular structures of the optimal proportion of carbon source materials under original conditions, after a 7-day static release experiment and after a 7-day denitrification experiment.

[0065] (5) Water samples were selected after 7 days of static release test and 7 days of denitrification experiment, and the supernatant was obtained by centrifugation. The dissolved organic matter was determined by three-dimensional fluorescence spectroscopy (3D-EEM). The excitation wavelength Ex was set to 220-450 and the scanning wavelength Em was set to 200-550 to evaluate the utilization of carbon source extract by microorganisms.

[0066] (6) After the denitrification test, the denitrification sludge in the conical flask was collected for microbial community analysis. Primers 338F and 806R (sequences shown in Table 2) were used to amplify the V3-V4 region of the denitrification sludge bacterial genome. The PCR products were subjected to high-throughput sequencing analysis using Illumina MiSeq, and the service was provided by Shanghai Meiji Biopharmaceutical Technology Co., Ltd.

[0067] Table 2 Primer sequences

[0068] Primer name Primer sequences 338F ACTCCTACGGGAGGCAGCAG 806R GGACTACHVGGGTWTCTAAT

[0069] result:

[0070] (1) Carbon release performance of composite carbon source

[0071] COD release of composite carbon source can be seen Figure 2 In (a) and (b), at 168h, the COD release of the CH group was between 392.50±9.37 and 457.00±11.32 mg / g, and the release of the RS group was between 350.50±7.79 and 368.50±4.50 mg / g. The COD release of the RS carbon source group showed a specific trend, that is, the COD release in the early stage of the experiment was significantly different (P<0.05), and when the experiment was carried out to 168h, there was no significant difference in the release (P=0.117-0.889). This may be due to the rapid release of the rice component in the new composite carbon source in the early stage, and the different contents showed differences in COD release. However, in the later stage, the rice stalks ended the rapid release period and entered the stable release stage. According to the release experiment results of agricultural waste materials, the total amount of COD released was less (72.00±2.08 mg / g), which was more affected by other components such as the PVA-SA gel skeleton.

[0072] Figure 2 (c) and (d) show the TN pollution release of the new composite carbon source. It can be seen that due to the screening of the previous comparative experiments, the TN release of the new composite carbon source is relatively low. The highest in the CH group is only 0.31±0.01 mg / g, and the highest in the RS group is only 0.24±0.02 mg / g, which indicates a low risk of secondary pollution.

[0073] (2) Denitrification performance of composite carbon source

[0074] like Figure 3 As shown in (a) and (b), the two new composite carbon sources from agricultural waste have excellent NO3- -N removal performance. In the experiment of 168h, two new carbon sources containing two different agricultural waste materials, CH group and RS group at all proportions can completely remove NO3 in SAT - -N; PVA-SA control group and sludge control group could not completely remove NO3 within 168h - -N, the final removal rates were 83.13±1.16% and 31.82±0.98%, respectively. Figure 3 (a) is a new composite carbon source containing CH groups, NO3 - -N removal rate, NO3 can be achieved in 120h - -N was completely removed, but in the first 96h of denitrification, the proportion of carbon source NO3 - -N removal efficiency still varies, especially at 48h. - -N removal rates were significantly different (P < 0.05), from high to low, they were CH2, CH1, CH3, CH4, and CH5, with corresponding removal rates of 73.54±0.90%, 67.74±0.79%, 63.86±0.80%, 51.97±0.95%, and 44.45±0.62%. At this time, the removal rates of the control group PVA-SA and the sludge group were 24.95±1.51% and 17.78±1.91% respectively. Figure 3 (b) is a new composite carbon source NO3 containing RS group - -N removal rate, as shown in the figure, the various proportions of carbon source NO3 in 0-72h - -N removal rates were similar until the 96th hour, when the NO3 - The removal rate of -N was much higher than that of other carbon sources (74.09±0.24%-91.26±0.30%) and the control (24.47±0.29%-62.48±1.01%) (P<0.01), which was 96.14±0.07%. Finally, at 144h, all composite carbon sources containing RS completed the removal of NO3 - Removal of -N.

[0075] Figure 3 Figures (c) and (d) show that the composite carbon sources containing CH and RS have good NH4+-N removal capabilities. At 120h, the addition of composite carbon sources has a significant effect on the removal of NH4 + The removal effect of -N was obvious. Except for CH1 (removal rate = 91.23 ± 0.35%), the composite carbon sources containing CH completely removed NH4 in SAT. + -N; The composite carbon source containing RS also had a good removal effect (removal rate = 95.14±0.27%-99.17±0.78%), while the removal rate of the control group was only 65.24±0.87%-68.38±1.33%.

[0076] The TN removal process of the composite carbon source containing CH was similar. After 168 h of denitrification experiment, the TN removal rate was 79.82 ± 0.58% - 85.72 ± 1.78%, and most of the TN removal occurred within 96 h (removal rate = 74.19 ± 1.26% - 80.91 ± 1.04%). Figure 3 (e)). Figure 3 (f) The removal rate is used to characterize the removal capacity of RS-containing composite carbon source for TN in SAT. - -N removal process is similar, and the removal effect of TN by various composite carbon sources containing RS in different ratios showed significant differences at 96h (P < 0.05), and they were arranged in descending order as RS3, RS5, RS4, RS2, and RS1, with removal rates of 80.10 ± 0.20%, 75.78 ± 1.07%, 69.27 ± 1.07%, 62.89 ± 0.31%, and 56.19 ± 1.61%, respectively. When the reaction was carried out for 168h, the TN removal rates of PVA-SA and sludge control groups were low, at 29.93 ± 3.35% and 15.44 ± 4.78%, respectively. At the same time, the TN removal rates of composite carbon sources containing RS were similar (P > 0.05), and were much higher than those of the control group, at 81.07 ± 0.25%-83.19 ± 0.92%, showing a significant effect on TN removal.

[0077] (3) Analysis of microbial community structure

[0078] Operational taxonomic units (OTUs) of sludge microorganisms after denitrification test with composite carbon sources containing CH and RS Figure 4 As shown in Figure 1. (a) In the denitrification experiment with CH composite carbon source, the number of OTUs shared by the sludge in each group was 762, and the sludge and PVA-SA control groups had the most unique OTUs sequences, 675 and 397, respectively. In the denitrification experiment with RS composite carbon source, the results were similar to those of CH. The sludge and PVA-SA control groups had the most unique OTUs sequences, and the number of OTUs shared was 902, as shown in Figure 1. (b).

[0079] The microorganisms in the sludge after the denitrification test with the composite carbon source containing CH and the control group were classified at the phylum level, such as Figure 5As shown in (a), the dominant bacterial colonies in the sludge in each group have certain similarities in structure and composition, mainly Firmicutes, Proteobacteria, Bacteroidota, Chloroflexi, Acidobacteriota, and Actinobacteriota. Their relative abundances in the control group CON are 47.11%, 9.34%, 6.77%, 10.48%, 6.31%, and 5.89%, respectively. After adding carbon source, denitrification showed gradient changes. In the groups CH1-CH5 containing new carbon source, the relative abundance of Firmicutes (62.69%-77.19%) and Proteobacteria (9.36%-17.67%) increased, while Chloroflexi (2.18%-2.97%), Acidobacteria (0.95%-2.26%), and Actinobacteria decreased (1.15%-1.94%). The relative abundance of Bacteroidetes in each group containing CH carbon source had great differences. CH2, CH3, and CH5 increased (7.26%-9.67%), while CH1 and CH4 showed a decrease in abundance (5.67%-6.07%). PVA-SA showed different patterns. The abundance of Firmicutes, Chloroflexus, Acidobacteria, and Actinobacteria decreased to 35.18%, 4.93%, 2.76%, and 1.84%, respectively, while the abundance of Proteobacteria (39.18%) and Bacteroidetes (6.95%) increased.

[0080] Figure 5 (b) shows the classification of each OTUs sequence at the genus level. The top four genera with higher relative abundance are Trichococcus, Bacillus, Clostridium, and Sporacetigenium, with relative abundances of 2.01%, 0.53%, 11.35%, and 4.99% in the control group CON, respectively. After adding CH1-CH5, the abundance of Trichococcus (33.09%-44.29%) and Bacillus (4.98%-16.95%) in the sludge increased, while the abundance of Clostridium (3.78%-6.76%) and Sporacetigenium (0.53%-1.62%) decreased. In PVA-SA, except for Bacillus which increased to 1.35%, the abundance of Trichococcus (0.52%), Clostridium (7.05%) and Sporacetigenium (3.09%) decreased. However, the abundance of Pseudomonas and Paenibacillus changed significantly, with relative abundances of 10.79% and 9.59% respectively.

[0081] The microorganisms in the sludge after the denitrification test with the composite carbon source containing RS and the control group were classified at the phylum level, such as Figure 6 As shown in (a), the dominant bacterial colonies in the sludge in each group showed high similarity in structure and composition with the groups containing the composite carbon source of CH, mainly Firmicutes, Proteobacteria, Bacteroidota, Chloroflexi, Acidobacteriota, and Actinobacteriota. After adding the composite carbon source containing RS for denitrification, there were different degrees of changes. Except for the relative abundance of Firmicutes in RS5 which was slightly reduced (45.74%), the other groups were There were different degrees of increase (47.42%-63.92%), among which RS3 had the highest and RS4 had the lowest; the relative abundance of Bacteroidetes increased in RS4 (7.59%) and RS5 (6.93%), and decreased in RS1 (6.49%), RS2 (3.79%), and RS3 (3.15%); the trends of the other dominant colonies were the same, that is, the abundance of Proteobacteria (16.9%-30.39%) in the RS1-RS5 groups increased, while the abundance of Chloroflexi (1.96%-4.60%), Acidobacteria (1.17%-4.55%), and Actinobacteria (1.98%-3.89%) decreased.

[0082] Figure 6 (b) shows the classification of each OTU sequence at the genus level. The four genera with the highest relative abundance are Clostridium, Bacillus, Trichococcus, and Sporacetigenium. The corresponding relative abundances in the control group CON are 11.35%, 0.53%, 2.01%, and 4.99%, respectively. After adding the new carbon source containing RS, the abundance of Clostridium in the sludge decreased (4.29%-10.92%) except RS1 (15.35%); the abundance levels of Sporacetigenium (1.65%-4.11%) in RS1-RS5 decreased, and Bacillus (2.04%-20.77%) increased; the relative abundance changes of Trichococcus in each carbon source group were quite different, RS1, RS2, and RS3 increased to 2.68%, 13.68%, and 25.73%, while RS4 (0.69%) and RS5 (0.73%) showed a decrease in abundance.

[0083] (4) Economic accounting analysis

[0084] At present, the price of PHA industrial raw materials is 20,000-30,000 yuan / ton. Corn husks and rice stalks are both agricultural wastes, so the material cost is set at 0.1 yuan / kg. Rice stalks are naturally dried when collected, and the average moisture content of corn husks is about 25%, which still needs to be dried. A 3000w rated power oven consumes 72kW·h of electricity for 24 hours, and can dry 20kg of corn husk raw materials each time. The electricity price in Guangzhou is 0.59 yuan / kW·h, so the price of dried corn husk raw materials is 2.8 yuan / kg. While maintaining effective water treatment capacity, the higher the content of agricultural waste, the lower the carbon source cost and the higher the economic efficiency.

[0085] Taking into account the denitrification and nitrogen removal performance, economy and microbial enrichment characteristics of the composite carbon source, CH2 and RS3 were selected for subsequent experiments, with the ratio of corn:PHA=2:1 and rice:PHA=1:1.

[0086] (5) Surface structure changes before and after carbon release and denitrification of composite carbon sources (SEM)

[0087] The surface morphology of the composite carbon source was characterized by SEM at 1000 times magnification. Figure 7 As shown. Among them, Figure (a) shows the initial state of the composite carbon source CH2. Its surface structure is dense and smooth with irregular round protrusions. The composite carbon source RS3 is initially dense and full. It can be seen that the PVA-SA skeleton after cross-linking and fixation is a full spherical structure evenly distributed in the carbon source as shown in Figure (b). Figures (c) and (d) are the surface structures of CH2 and RS3 after carbon release. It can be seen that the smooth surface of CH2 disappears, the PVA-SA skeleton is exposed, and gaps appear in the dense structure; similarly, gaps appear in the RS3 structure, and it can be seen that the remaining rod-like structure of the rice stalk is still intact, and the surface is regular and serrated. In CH2 and RS3 after carbon release, it was found that part of the spherical structure of the PVA-SA skeleton was broken, and the short rod-like components overflowed, but the overall structure of the carbon source was three-dimensionally complete. After denitrification, under the action of microorganisms, the decomposition and consumption of carbon sources intensified. In Figures (e) and (f), the three-dimensional surface structures of the composite carbon sources CH2 and RS3 were destroyed. The surface of the CH carbon source collapsed and a large number of pores appeared, while the surface of the RS was smooth. The original rod-shaped structure of the remaining rice stalks was blurred.

[0088] (6) Quality analysis of composite carbon source leaching solution before and after microbial utilization (3D-EEM)

[0089] The leaching solution of the carbon release experiment of composite carbon sources CH2 and RS3 and the supernatant of SAT after denitrification were selected, and the protein-like and humus-like components and contents were detected by three-dimensional fluorescence spectroscopy (3D-EEM). The results are as follows Figure 8As shown. Figure (a) is the CH2 composite carbon source leachate, which mainly shows two characteristic fluorescence peaks, namely peak A Ex / Em = 280 / 320 and peak B Ex / Em = 230 / 330, representing soluble microbial metabolites and tyrosine proteins, respectively. Similar to CH2, the RS3 composite carbon source leachate also has a peak A Ex / Em = 270 / 340. In addition, there are also absorption characteristic peaks C peak Ex / Em = 220 / 360 and D peak Ex / Em = 340 / 440 representing tryptophan proteins and humic acid-like proteins, see Figure (b).

[0090] After denitrification, the fluorescence peak intensities of peak A Ex / Em = 280 / 320 and peak B Ex / Em = 220 / 320 in the supernatant of the CH2 composite carbon source were enhanced. The fluorescence intensities of peak A Ex / Em = 270 / 340 and peak D Ex / Em = 300 / 420 in RS3 were enhanced, and at the same time, a characteristic absorption peak of tyrosine proteins that was not present in the leaching solution appeared, namely peak B Ex / Em = 220 / 320.

[0091] (7) Characteristics of functional group changes before and after composite carbon source microbial utilization (FTIR)

[0092] FTIR was used to analyze the static release of composite carbon sources CH2 and RS3 and the changes in chemical composition and functional groups before and after denitrification. Fig. 9 As shown in (a), after carbon release and denitrification, CH2 and RS3 showed highly similar typical functional group bands at 3300 cm -1 Represents OH stretching; 2932cm -1 The -CH stretching vibration on the saturated carbon; 1721cm caused by C=O and C=C stretching vibration -1 、1643cm -1 Absorption peak: 1278cm -1 The stretching vibration of phenolic CO; the stretching vibration of alcohol CO appears at 1053cm-1 absorption peak, the absorption peak at 979cm-1 bending vibration of olefin CH. In addition, the 1721cm in CH2 and RS3 can be seen -1 and 1278cm -1 The absorption peak after denitrification was weaker than that after carbon release.

[0093] 3. Study on the solid-phase nitrification performance of composite carbon sources under different HRT

[0094] (1) Select CH2 (corn: PHA = 2:1) and RS3 (rice: PHA = 1:1) composite carbon sources, select volcanic rock as the supporting layer, and use ultrapure water to soak and wash three times to clean the surface impurities.

[0095] The experimental reactor is made of organic glass, with an inner diameter of 9 cm, a total height of 42 cm, a reaction zone height of 7.9 cm, a support layer height of 7.9 cm, and an effective volume of 0.5 L. Four sampling ports are arranged between the water inlet and outlet of the reactor to detect the operation of the reactor and ensure the quality of the effluent. The interval between the sampling ports is 7.86 cm. The bottom is supported by volcanic rocks, and the reactor adopts a bottom water inlet and top water outlet mode to facilitate the microorganisms to fully denitrify and discharge gases to create an anaerobic environment.

[0096] (2) Experimental methods:

[0097] Reactor construction: To prevent algae from growing, the entire experiment was conducted in a dark room. First, fill in 0.5L of volcanic rock as the reactor support layer, take 20ml of washed sludge and wrap it with gauze, place it on the reactor support layer, then fill in 0.5L of dried composite carbon source, connect the water inlet tank to the bottom water inlet through a peristaltic pump water pipe, and complete the construction.

[0098] The characteristics of the sludge after washing are shown in Table 3:

[0099] Table 3 Sludge characteristics

[0100]

[0101] Sludge acclimation and biofilm formation: After the reactor was built, the peristaltic pump was pumped into the artificial synthetic aquaculture simulated tail water. The SAT composition and concentration were shown in Table 4. - -N is completely removed and there is no NO2 - -N accumulation, discharge all the sewage in the reactor and then pump in SAT, repeat three times, it is considered that the sludge acclimation is completed and the reactor is started after biofilm formation.

[0102] Table 4

[0103]

[0104]

[0105] (4) Reactor operation: CH2 and RS3 composite carbon sources were used, and four HRT treatment groups were set up in each. The peristaltic pump controlled the SAT inlet flow rate to control the HRT to 4, 8, 12, and 24 h, respectively. The groups were numbered according to the type of composite carbon source and different HRT, and were recorded as CH4h, CH8h, CH12h, CH24h and RS4h, RS8h, RS12h, and RS24h, respectively. Each reactor was operated independently for 60 days, and water samples from the top water inlet were continuously collected at 1, 2, 3, 4, 5, 6, 7, 9, 11, 13, 15, 17, 20, 23, 26, 30, 35, 40, 45, and 50 days.

[0106] The method for detecting hydration index is shown in Table 5:

[0107] Table 5

[0108] Measurement items Determination method TN Alkaline potassium persulfate digestion UV spectrophotometry TP Alkaline potassium persulfate digestion UV spectrophotometry COD Acidic potassium dichromate oxidation method <![CDATA[NO3 - -N]]> Phenol disulfonic acid method <![CDATA[NH4 + -N]]> Salicylic acid spectrophotometry <![CDATA[NO2 - -N]]> N-(1-naphthyl)ethylenediamine spectrophotometry

[0109] On the 50th day, the gauze package at the bottom was removed and the denitrification sludge was collected for high-throughput sequencing analysis of microbial 16S rRNA.

[0110] (5) Results

[0111] (5.1) Denitrification effect of composite carbon source at different HRT of CH2 composite carbon source

[0112] Using CH2 composite carbon source as filler, a sequencing batch reactor was built, and the denitrification situation was as follows Fig.10 (a) is the corresponding NO3 in the reactor for 50 days at hydraulic retention time of 4h, 8h, 12h, and 24h - -N removal rate. The average removal rates were 51.25±3.12%, 57.57±3.26%, 92.78±1.17%, and 97.06±1.65%, respectively. The difference analysis showed that the removal rate of NO3 - -N average removal rate was not significantly different (P = 0.075); NO3 - -N average removal rate had no significant difference (P = 0.231). The average removal rate of NO3--N at HRT of 12h and 24h was significantly higher than that at 4h and 8h (P < 0.01). The change of TN removal rate within 50 days of operation is shown in Figure (b). The average removal rates from high to low were 46.15 ± 2.45%, 55.05 ± 3.17%, 81.36 ± 1.72%, and 84.90 ± 2.07%, respectively. There was no significant difference between CH12h and CH24h (P = 0.313).

[0113] Fig.11 NO2 during the operation of the reactor - -N accumulation, NO2 within 50 days - The average concentrations of -N from high to low were CH8h (1.12±0.23mg / L), CH4h (0.51±0.09mg / L), CH12h (0.09±0.04mg / L), and CH24h (0.04±0.04mg / L), among which there was no significant difference between CH12h and CH24h (P=0.797). In addition, during the operation of CH8h, the effluent NO2 - -N concentration changes greatly, showing a significant increase around the 13th and 45th days, reaching a maximum of 3.00 mg / L. At the same time, it can be seen that CH4h and NO2 -The trend of increasing -N accumulation was gradually obvious, while CH24h maintained extremely low effluent NO2 throughout the experimental period. - -N concentration.

[0114] (5.2) Denitrification effect of composite carbon source at different HRT of RS3 composite carbon source

[0115] Fig.12 Part (a) shows the NO3 content in the RS3 packed reactor at four different HRTs for 50 days. - -N removal rate, NO3 - The average removal rates of -N from high to low were RS24h, RS12h, RS8h, and RS4h, and the corresponding average removal rates were 95.78±1.43%, 90.48±1.47%, 71.22±4.24%, and 47.67±3.01%, among which the average removal rates of RS24h and RS12h were not significantly different (P=0.179), and both were significantly higher than RS8h and RS4h (P<0.01). The changes in TN removal rate within 50 days of operation are shown in Figure (b). The average removal rates from high to low were RS24h (86.49±1.43%), RS12h (79.22±1.83%), RS8h (68.47±3.47%), and RS4h (44.01±2.49%). Among them, the TN removal rate of RS12h increased after 30 days, reaching a level comparable to that of RS24h.

[0116] Reactors containing RS3 packing had lower NO2 at both 4 and 8 h HRT - -N accumulation. Among them, NO2 - The accumulated concentration of -N showed an overall increasing trend with the increase of the reactor operation time, and RS8h reached a maximum of 1.44±0.02mg / L within 50 days of operation, while RS12h and RS24h maintained a low effluent NO2 concentration throughout the experimental period. - -N concentration level. Overall, the average NO2 in RS8h (0.46±0.12mg / L) and RS4h (0.44±0.11mg / L) within 50 days - The average concentration of -N accumulation was not significantly different (P = 0.897), both higher than RS12h (0.06 ± 0.02 mg / L) and RS24h (0.01 ± 0.02 mg / L), which were similar (P = 0.660). Fig.13 shown.

[0117] (5.3) Analysis of microbial community structure

[0118] The operational taxonomic units (OTUs) of microorganisms in the reactor filled with CH2 and RS3 are as follows: Fig.14 The number of common OTUs was 84, and the RS24h and CH12h groups had the most unique OTUs sequences, 149 and 49, respectively.

[0119] The microorganisms in the sludge after the denitrification experiment in the reactor with CH2 and RS3 as fillers were classified at the phylum level, such as Fig.15 As shown, the main phyla are Proteobacteria, Firmicutes, Campylobacterota, Bacteroidota, and Desulfobacterota. In the CH2-filled reactor, their relative abundances are 50.93%-86.48% for Proteobacteria, 3.16%-13.81% for Firmicutes, 0.62%-37.39% for Campylobacterota, 0.61%-6.37% for Bacteroidetes, and 1.34%-10.65% for Desulfobacterota. The relative abundance of Campylobacterota in CH12h and CH24h is higher than that in CH4h and CH8h, and the relative abundance of Desulfobacterota (10.65%) in CH12h is higher than that in the other groups. Similarly, in the reactor with RS3 as the filler, the relative abundance of Proteobacteria was 16.45%-86.38%, Firmicutes was 3.67%-55.28%, Campylobacter was 0.99%-11.13%, Bacteroidetes was 3.46%-13.10%, and Desulfobacteria was 1.42%-10.39%. Among them, the relative abundance of Firmicutes and Desulfobacteria in RS12h and RS24h were higher than those in RS4h and RS8h. It is worth noting that the relative abundance of Firmicutes in RS24h was the highest, reaching 55.28%, which was much higher than Proteobacteria (16.45%), and was different from the other groups.

[0120] In order to further understand the microbial structure composition of sludge after denitrification experiment in reactors with CH2 and RS3 as fillers, the microorganisms were classified at the genus level, e.g. Fig.16As shown in the figure, the dominant genera in each CH2 group mainly included Dechlorobacter, Zoogloea, Sulfurospirillum, etc., with the corresponding relative abundances of 34.28%-47.33%, 2.00%-39.84%, and 0.62%-37.39%, respectively. When the HRT was extended to more than 12h, the relative abundance of Sulfurospirillum increased (10.84%-37.39%). Except for RS24h, which had a richer community structure, the main dominant bacterial genera in the sludge at other HRTs in the RS3 reactor were similar to those in the CH2 groups, with abundances of Dechlorobacter (22.24%-44.25%), Zoogloea (26.72%-46.55%), and Sulfomonas (0.98%-11.13%). When the HRT was extended to 12h, the relative abundance of Sulfomonas in RS12h increased to 11.13%, which was consistent with the change trend of the CH2 groups.

[0121] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a composite carbon source, characterized in that: The following steps are involved: The artificial polymer PHA and agricultural waste are added to the hydrogel skeleton, and after freeze-forming, they are added to the cross-linking agent for cross-linking, and then washed and dried to obtain a composite slow-release carbon source; The agricultural waste includes corn husk carbon source or rice straw carbon source; The mass ratio of the artificial polymer PHA to the agricultural waste is (1-3): (3-1).

2. The method for preparing a composite carbon source according to claim 1, characterized in that: The hydrogel skeleton is a polyvinyl alcohol-sodium alginate hydrogel skeleton, and the specific preparation method comprises the following steps: The polyvinyl alcohol and sodium alginate are mixed, water is added and stirred evenly, the mixture is heated in a water bath once, then allowed to stand, and then heated in a water bath twice to obtain the polyvinyl alcohol-sodium alginate hydrogel skeleton.

3. The method for preparing a composite carbon source according to claim 2, characterized in that: The mass ratio of the polyvinyl alcohol, sodium alginate and water is 32:3:

400.

4. The method for preparing a composite carbon source according to claim 2, characterized in that: The temperature of the water bath heating is 95°C and the time is 10 minutes; The temperature of the secondary water bath heating is 95°C and the time is 15 to 20 minutes; The standing time is 12 hours.

5. The method for preparing a composite carbon source according to claim 1, characterized in that: The cross-linking agent is a saturated H3BO4 solution containing 5% CaCl2.

6. The method for preparing a composite carbon source according to claim 1, characterized in that: The cross-linking temperature is 4°C and the time is 24 hours.

7. A composite carbon source prepared by the method for preparing a composite carbon source according to any one of claims 1 to 6.

8. Use of a composite carbon source as claimed in claim 7 in the treatment of aquaculture tail water.

Citation Information

Patent Citations

  • Environment-sensing composite slow-release carbon source as well as preparation method and application thereof

    CN118878078A